A futuristic discourse of higher education system linkages with the labour markets in the Kingdom of Saudi Arabia. (29th November 2010) - Aldosary, Adel S.; Nahiduzzaman, Kh.Md.
This research paper reports on the policy analysis of higher education policy debate together with a survey conducted among the alumni of College of Environmental Design (CED) at King Fahd University of Petroleum and Minerals (KFUPM). The Kingdom of Saudi Arabia (KSA) is accelerating its development procedures in all levels with the priority towards the human resources development (HRD). On account of which, the Government of KSA established schools, universities and training centres in every city to reduce the augmented reliance on the rising foreign workforce that is in many ways creating unemployment among the Saudi labour. This research emphasises to explore the linkages and gap between the higher education system in KSA and the facts behind the employer demands for skilled human resources in the labour market. This is concluded by making a futuristic recommendation aimed at facing the challenge of protecting local workforce from being unemployed.